(untitled) (Journal of the College of Basic Education, 2022)
Research The current research aims to develop the gestural skills of the students of the Institute of Fine Arts in the subject of innovation and silence. Experimental research tool (observation form) was adopted by its design and found to be honest and reliable. After the application of the program, the appropriate statistical methods were used and concluded that there is a significant impact of the training program in the development of gestural skills, and accordingly recommended its adoption.